Cardiovascular Risk Reduction Comparison of Felodipine and Propranolol in Patients of Essential Hypertension (Medical Forum Monthly, 2024)
Objective: To compare the efficacy of felodipine versus propranolol in patients of essential hypertension for Serum cholesterol, LDL cholesterol and HDL cholesterol.Study Design: Randomized controlled study.Place and Duration of Study: This study was conducted at the Accident and Emergency Department, Bahawal Victoria Hospital, Bahawalpur and Ansari Private Clinic Model Town B Bahawalpur from 1st July 2015 to 30th September 2015.Materials and Methods: Total 90 patients with essential hypertension having age range from 30 to 50 years were enrolled in this study for three months. Patient were randomly divided into three groups I, II and III, each group comprising 30 patients. Group I patients were treated with felodipine, Group II patients were treated with propranolol and group III patients were treated with placebo. Effects of these drugs on Lipid profile(Serum cholesterol, HDL cholesterol and LDL cholesterol)were compared.Result: Felodipine, treated patients exhibited markedly significant fall in the serum cholesterol (P<0.01), highly significant fall at the level of LDL cholesterol (P<0.001) and non-significant effect in HDL cholesterol. Whereas propranolol treated patients showed highly significant increase of serum cholesterol (P<0.001), markedly significant increase in LDL cholesterol (P<0.01) and markedly significant decreased in HDL cholesterol (P<0.01).Whereas comparison of two drugs Felodipine and Propranolol displayed a highly increased (P<0.001) serum cholesterol, LDL cholesterol and markedly increased (P<0.01) HDL cholesterol.Conclusion: Result of this study showing that comparing the two drugs felodipine had significantly decreased Serum cholesterol and LDL Cholesterol, whereas propranolol increased the Serum cholesterol, LDL cholesterol and decreased HDL cholesterol. So felodipine prove its merit over propranolol.